A mobile application to provide personalized information for mobility impaired tourists - Ribeiro, Fernando Reinaldo (2018)
This is a pre-copyedited version of a contribution published in Rocha A., Adeli H., Reis L.P., Costanzo S. (eds) Trends and Advances in Information Systems and Technologies. WorldCIST'18 2018 published by Springer. The definitive authenticated version is available online via https://doi.org/10.1007/978-3-319-77712-2_16